ORIENTATION ON IMPLEMENTATION OF LEARNING CURRICULUM AT SENIOR HIGH SCHOOL: TEACHER'S PERSPECTIVE - Zulhafizh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by learning activities that cannot be done arbitrarily but must refer to the applicable curriculum. A teacher must be able to conduct orientation activities in implementing the curriculum in educational units to meet the maximum curriculum demands. The aim is to find out the orientation capabilities of the teacher. The action was carried out with a descriptive qualitative approach. The main instrument used for data collection was a questionnaire. The research sample was 108 teachers of senior high schools in Pekanbaru. Data analysis was performed by observing each questionnaire item that was filled out by the respondents. The results of the analysis showed that running the applicable curriculum in the education unit scored 3.93; sorting out content according to future demands scored 3.92; looking for material according to curriculum demands scored 4.50; adjusting curriculum requirements to the conditions and environment scored 4.51; and preparing various learning devices scored 4.70. The average teacher's ability in the context of orienting the implementation of the learning curriculum was 4.31, categorized as very high. The teachers try positively and significantly to carry out the demands of the curriculum to the maximum. The success of the learning curriculum lies in the success of the teacher in following and implementing it in the field. Various skills, knowledge, and experience also influence the teacher in carrying out the demands of the curriculum.Keywords: , , ,